Kinerja Pertumbuhan Ikan Gabus (Channa striata) Dengan Penambahan Suplemen Astaxanthin Pada Level Berbeda - Sofian sofian; Syaeful Anwar; Merza Saputra (Jurnal Akuakultur Rawa Indonesia, 2019)
This study aimed to evaluate the effect of different levels dietary asatxanthin supplementation on growth performance of Snakehead. This research was used completely randomized design and be repeated three times. The fish used are natural source with average body weight of 2,90±0,17 g. Fish were reared for 30 days in sized nets 100x100x50 cm3. The experimental obeserved were different levels astaxanthin supplementation, namely; 0, 100 and 200 mg/kg diet. The result showed that, fed on the diet supplemented with astaxanthin 200 mg/kg diet produced the best final weight, daily growth rate and feed efficiency (8.24 g, 4.14% and 85.31%). The supplementation astaxanthin 100 and 200 mg/kg diet did not affect on survival rate of snakehead